Respuesta :
Answer:
C) 3 - i√13
Step-by-step explanation:
x² - 6x = -22
x² - 6x + (-6/2)² = -22 + (-6/2)²
x² - 6x + 9 = -22 + 9
(x - 3)(x - 3) = -13
x - 3 = ± √-13
x - 3 = ± i√13
x = 3 ± i√13
x = 3 + i√13 & x = 3 - i√13
Answer:
The solution of given equation are 3±√13i.
Step-by-step explanation:
We have given a quadratic equation.
x²-6x = -22
We have to find the solution of given equation.
We use method of completing square to solve this.
Adding (-3)² to both sides of given equation, we have
x²-6x+(-3)² = -22+(-3)²
(x-3)² = -22+9
(x-3)² = -13
Taking square root to both sides of above equation, we have
x-3 = ±√-13
x-3 = ±√13i where i = √-1
x = 3±√13i
Hence, the solution of given equation are 3±√13i.